Implentasi Algoritma RSA Untuk Aplikasi Enkripsi Dan Dekripsi Citra Dua Dimensi Berbasis Web (Studi Kasus: PT. Intigarmindo Persada) - Deshinta Ariani; Dimas Abisono Punkastyo (CV. Multi Kreasi Media, 2023)
Sample design image data is a design proposal for clothes or accessories made by the design team of PT Intigarmindo Persada which contains information about the size, pattern, color, and materials that will be needed in production. In order to secure sample design image data from information leakage, a system is needed that can encode sample design image data so that confidentiality is maintained. This study will implement the rivest shamir adleman (RSA) cryptographic algorithm for the design of encryption and decryption applications of web-based two-dimensional image data using waterfall development methods. This research resulted in two-dimensional encryption and decryption application of image data that can minimize information leakage from sample design image data. The test results show that the RSA algorithm can secure image data into unreadability and return it to its original form.